Biomechanical aspects of nonspesific low back pain - Harrianto, Ridwan (Universa Medicina, 2010)
Low back pain (LBP) is a common problem in adult life, since despite its benign nature it is commonly associated with incapacity, productivity loss due to sick leave, and correspondingly high costs to the individual worker. Psychosocial and lifestyle factors and work-place exposures have been implicated in the onset of symptoms. Heavy physical work, static work postures, frequent bending and twisting, lifting and postural movements, repetitive work, and whole body vibrations are occupational factors associated with LBP. The usual classification of LBP is related to the duration of the complaints (acute, subacute, and chronic). However, these terms fail to take into account several clinically important aspects of the course of LBP, which is frequently recurrent and thus neither acute nor chronic. More realistically, LBP should be classified as specific and nonspecific. Approximately 90% of LBP cases have no identifiable cause and is designated nonspecific LBP. However, despite its high prevalence, the etiology and nature of nonspecific LBP are not yet well understood. Its pathophysiology remains complex and multifaceted. Multiple anatomic structures and elements of the lumbar spine (e.g. bones, ligaments, tendons, discs, and muscles) are all suspected of playing a role. Many of these components of the lumbar spine have sensory innervations that can generate nociceptive signals in response to tissue-damaging stimuli. Other causes could be neuropathic (e.g. sciatica). Some cases of LBP most likely involve mixed nociceptive and neuropathic etiologies.